GLOBAL CHALLENGES AND IMPERATIVES FOR THE DEVELOPMENT OF INTERCULTURAL COMMUNICATION - AKSYONOVA, Oksana; YATSENKO, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article is dedicated to the study of aspects of intercultural communication in the contemporary global environment. The aim of the article is to analyze the impact of globalization processes on intercultural communication, identify the challenges of intercultural communication, and justify ways to overcome them. The article discusses the concept of intercultural communication in the modern globalized world. The study analyzes existing theoretical approaches to the analysis of intercultural exchange. It is revealed that intercultural communication is not only a verbal exchange of information but also a complex process of cultural interaction, which includes sociocultural norms, behavioral patterns, and interpersonal interaction. It is defined that the primary aspect of intercultural communication is the ability to correctly interpret cultural differences and adapt one’s behavior to a specific cultural context. In a globalized world, communication between cultures requires a high level of intercultural competence, which includes the ability to communicate effectively with people from different cultures, understand their views and norms, and adapt one’s communication strategy to the specific demands of various sociocultural contexts. The article analyzes global challenges in the process of intercultural communication, particularly identifying that global intercultural communication leads to cultural unification, social inequality, and creates risks of conflicts. To overcome the aforementioned challenges of global intercultural communication, it is proposed to: develop intercultural education to foster tolerance, critical thinking, and the ability for constructive communication with people from different cultural traditions; implement new strategies to promote effective intercultural dialogue through the integration of modern information technologies; create international platforms, develop international projects, forums, and conferences for exchanging experiences and ideas, which will enable collaboration between cultures and address global issues such as climate change, peacekeeping, and economic development; and implement intercultural business strategies that take cultural peculiarities into account, to reduce the risks of misunderstandings and conflicts in international communications.